2017
DOI: 10.1111/1365-2664.13046
|View full text |Cite
|
Sign up to set email alerts
|

Abandoned pastures cannot spontaneously recover the attributes of old‐growth savannas

Abstract: Active restoration strategies have been recommended to recover Neotropical savannas in abandoned lands, but no studies have investigated the trajectories and speeds of spontaneous recovery for these systems. Research into the dynamics of degraded savannas is urgently needed to guide restoration decision making. We analysed the dynamics of secondary savannas in the Brazilian Cerrado by sampling 29 abandoned pastures (time since abandonment ranging from 3 to 25 years) and applying the space‐for‐time substitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 67 publications
(107 reference statements)
1
60
0
4
Order By: Relevance
“…Overgrazing, fire exclusion, and woody encroachment can replace tropical old-growth grasslands with low-diversity swards of exotic grasses or dense tree cover in a matter of years to a few decades (e.g. Cava et al, 2018). Grassland conversion for agriculture, plantation forestry, or mining not only destroys plant and animal communities, but also profoundly changes chemical and physical soil features Le Stradic et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overgrazing, fire exclusion, and woody encroachment can replace tropical old-growth grasslands with low-diversity swards of exotic grasses or dense tree cover in a matter of years to a few decades (e.g. Cava et al, 2018). Grassland conversion for agriculture, plantation forestry, or mining not only destroys plant and animal communities, but also profoundly changes chemical and physical soil features Le Stradic et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Yet in the absence of fire, exotic-dominated tropical grasslands will become low-diversity forests. Indeed, across a chronosequence of abandoned pastures invaded by African grasses in Brazil, Cava et al (2018) found that herbaceous savanna plants did not spontaneously regenerate and that fire exclusion promoted the formation of low-diversity forests, which lacked the historical old-growth savanna structure and species composition. Further complicating matters, exotic grass invasions can be promoted by cattle, which disperse seeds and influence apparent competition between native and invasive species (e.g.…”
Section: (6) Afforestation and Invasive Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilizers and agricultural limestone are commonly added to enrich soil and neutralize acidity, frequently favoring invasions by exotic grasses (Bustamante et al ). Pastures are typically seeded with highly competitive exotic grass species, which rapidly spread into agricultural fields and degraded areas, increasing fire frequency (Pivello et al ), outcompeting native species, and decreasing the resilience of the herbaceous layer (Cava et al ; Silva & Vieira ; Coutinho et al ).…”
Section: Determinants Of Grassland‐savanna‐forest Complex In Cerrado mentioning
confidence: 99%
“…Land use changes are intrinsically uncertain to model, and difficult to reverse since, for example, pasture abandonment does not lead to the spontaneous restoration of original old-growth ecosystems [79]. Despite the fact that conversion of pasture to annual crops is the most frequent conversion in Brazil [80], its conversion to forest or perennial bioenergy crops is likely to promote many environmental benefits, including the increase in soil carbon stocks [81,82].…”
Section: Climate Impacts From Changes In Land Usementioning
confidence: 99%